A study to analyse the effective technique to reduce Hamstring tightness among four techniques in female physiotherapy students - V.RAJALAXMI,; K.ANUSIYA,; S.RAMACHANDRAN,; G.YUVARANI, (International Journal of Pharma and Bio Sciences, 2017)
Flexibility in hamstrings muscle group is necessary for the hip and knee movements as well as in many functional activities and in prevention of injury in which muscle group is elongated over hip and knee simultaneously.The purpose of the study is to compare the effect of four types of hamstring stretching on hamstring tightness. Flexibility is an ability to move a single joint or a series of a joint smoothly and easily through and unrestricted, pain free range of motion. The hamstring muscle group is necessary for knee & hip movement as well as in many functional activities and in prevention of injury in which muscle group is elongated over the hip and knee simultaneously. Many factors influences an individual’s flexibility like age, race, gender, tissue temperature strength training, stiffness and warm up have influenced flexibility. A proper stretching program is key to improving flexibility. To get maximum flexibility it must be repeated 5 times per day for 2 sessions /day, 5 days/ week for 4 weeks. In the experimental study a total of 60samples were selected by simple random sampling method who met the inclusion criteria out of 100 healthy young female individuals between the age group of 18-21years who volunteer themselves for the study [15 individual in each group].Group A: 90-90 Passive stretching, Group B: 90-90 Active stretching, Group C: PNF stretching, Group D: Self stretching. It’s a Comparative study, Pre and post test design conducted among female Physiotherapy students in Dr.MGR. Educational and Research Institute University. On comparing mean value of four groups on active knee extension test (AKET) shows significant reduction in the post test mean but Group C PNF stretching (hold relax) shows (16.57) lower mean value is more effective than other three groups at ***p≤0.0001.Hence alternate hypothesis is accepted.